2008
DOI: 10.1088/0256-307x/25/2/112
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of the Download Network

Abstract: The scaling behavior of fluctuation for a download network which we have investigated a few years ago based upon Zhang's Encophysics web page has been presented. A power law scaling, namely σ ∼ f α exists between the dispersion σ and average flux f of the download rates. The fluctuation exponent α is neither 1/2 nor 1 which was claimed as two universal fluctuation classes in previous publication, instead it varies from 1/2 to 1 with the time window in which the download data were accumulated. The crossover beh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A composite sponge with uniformity pore size and a smooth surface was obtained and it had a certain effect in the hemostatic process. Ye Ding [13] used the mixture of calcium alginate and chitosan prepared a sponge dressing. It was the first time that someone use the electrostatic interactions between the positively charged of the chitosan and the anion of the sodium alginate to prepared chitosan -calcium alginate fibers and then structure the reticular sponge.…”
Section: Research Status Of Spongy Medical Dressingsmentioning
confidence: 99%
“…A composite sponge with uniformity pore size and a smooth surface was obtained and it had a certain effect in the hemostatic process. Ye Ding [13] used the mixture of calcium alginate and chitosan prepared a sponge dressing. It was the first time that someone use the electrostatic interactions between the positively charged of the chitosan and the anion of the sodium alginate to prepared chitosan -calcium alginate fibers and then structure the reticular sponge.…”
Section: Research Status Of Spongy Medical Dressingsmentioning
confidence: 99%
“…In addition, Barabasi found the relationship between the average and standard deviation of network nodes' flow [5], and physicists call this relationship as fluctuation scaling (FS) [6]. Many studies have found that the dissemination process on complex networks exist fluctuations scaling characteristics [7]- [10].…”
Section: Introductionmentioning
confidence: 99%